Geospace: The naturally occurring plasma laboratory - Longley, William J.; Goodwin, Lindsay V. (Frontiers in Astronomy and Space Sciences, 2022)
While the societal relevance of space physics drives most of the research in the field, this paper argues for the merit in addressing problems that are core to plasma physics, regardless of discipline or application to society. The geospace environment is a unique, naturally occurring laboratory that can be used for investigating basic plasma processes. Ground and satellite-based observations provide important data for understanding basic plasma processes such as transport, charge-neutral interactions, collisions, and turbulence. These are important topics in space physics, and we show how these topics are relevant to the broader plasma physics community. This paper recommends improved funding lines to examine fundamental plasma physics in the geospace environment. This can be accomplished by annual solicitation of the NASA ROSES B.3 Heliophysics Theory, Modeling, and Simulations (HTMS) program; consideration of plasma physics as relevant to all NASA proposals; and creating a pathway for high-risk research into fundamental science.